Comparison of Team Based and Traditional Teaching Methods in Forensic Medicine: on the Basis of Assessment Tools - Shahid Kamran; Muhammad Sajid Khan; Jamil Ahmed Siddiqui; Natasha Mustafa; Waqar Shaikh; Hina Khan (Journal of Bahria University Medical and Dental College)
Objective: To compare two different teaching methods in Forensic Medicine on the basis of assessment tools. Study design and setting: A cross sectional analytical study was conducted at the Department of Forensic Medicine at Al-Tibri Medical College and Hospital, from February to August 2019 Methodology: Total 100 students of third year MBBS were included in this study after taking ethical approval from the ethical review committee. These students were randomly divided into two groups of 50 students each, with Group A being taught through the traditional didactic lectures and Group B by Team Based Learning (TBL). Both groups were assessed using different assessment tools. Each assessment was of 25 marks and for comparison of marks, independent “t” test was applied comparing the mean value through SPSS version 20.0 and the level of significance was taken at < 0.05. Results: The student’s involved in Team Based Learning performed superior than teacher centered strategy. In Group A, the students were taught via traditional lecture-based method and Group B was introduced to Team Based Learning. The mean score of assignment in Group A and Group B showed P value <0.001 that showed significantly higher grades in student-centered teaching. Conclusion: Team based learning showed significant successful results in all assessment methods, therefore, it has been concluded through our study that Team Based Learning is a more effective method of teaching Forensic Medicine and it helps in making learner autonomous.